If n → ∞ lim ( ln 2 − ( − 2 1 + 3 1 − 4 1 + ⋯ − n ( − 1 ) n ) ) n has α number of limits and l 1 , l 2 , l 3 , ⋯ l k be the limits for some positive integer k , find the value of j ≤ α ∑ ( 1 ≤ i ≤ k ∑ l i ) j .
This problem, taken from Romanian Mathematical Magazine , was proposed by Mohammed Bouras, Morocco .
The original proposed problem supposed to prove all the limits of it.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
I wish to share my one of those two proposed solutions. If any errors or typo are spotted in the solution I would be glad to be corrected.
we will show that the there exist two different limits for above problem.
For 0 < x ≤ 1 , we define the functions f ( x ) = ln ( 1 + x ) , g ( x ) = k = 1 ∑ n k + 1 ( − x ) k and we note that f ( x ) − g ( x ) = x − k = 2 ∑ ∞ ( − 1 ) k + n k + n x k + n = x + k = 2 ∑ ∞ ( − 1 ) k + n ∫ 0 x t k + n − 1 d t = x + ( − 1 ) n ∫ 0 x t n ( k = 1 ∑ ∞ ( − 1 ) k t k − 1 ) d x = x − ( − 1 ) n ∫ 0 x 1 + t t n d t hence for x = 1 we have then f ( 1 ) − g ( 1 ) = ln ( 2 ) − k = 1 ∑ ∞ k + 1 ( − 1 ) k = 1 − ( − 1 ) n ∫ 0 1 1 + t t n d t Now we shall show that n → ∞ lim ( f ( 1 ) − g ( 1 ) ) n = { e if n ∈ 2 n − 1 e 1 otherwise
We solve the following integral for any 0 ≤ m ≤ n . By polynomial long division it is trivial to note that ∫ 0 1 t + 1 t m d t = ( − 1 ) m ∫ 0 1 ( t + 1 1 − 0 ≤ j ≤ m ∑ ( − 1 ) j t j − 1 ) d t and hence on integrating ∫ 0 1 1 + t t m d t = ( − 1 ) m ⎝ ⎛ lo g ( 2 ) − 1 ≤ j ≤ k ∑ j ( − 1 ) j + 1 ⎠ ⎞ = 2 − 1 ( ψ ( 2 n + 1 ) − ψ ( 2 2 n + 1 ) ) = 2 1 ( H 2 n − H 2 n − 1 ) Further we note that H n ≈ γ + ln n + 2 n 1 − O ( n 2 ) with which we deduce that H 2 n − H 2 n − 1 ≈ n 1 − ln ( n n − 1 ) + n − 1 1 for all n > 1 and hence H 2 n − H 2 n − 1 → n 1 as n gets larger. Thus we have for n → ∞ lim ( f ( 1 ) − g ( 1 ) ) n = n → ∞ lim ( 1 − 2 n ( − 1 ) n ) n = e − 2 ( − 1 ) n = e − ( − 1 ) n therefore if n is even we have limit as e 1 and if n is odd we have limit e .
As α = 2 and l 1 = e 1 and l 2 = e . Finally 1 ≤ j ≤ α ∑ ( 1 ≤ i ≤ k ∑ l i ) j = e + e 1 + ( e + e 1 ) 2 ≈ 7 . 3 4 1 4 .